Evaluation de quelques paramètres dendrométriques de Guarea cedrata (A. Chev.) Pellegrin en plantations Blanc-étoc et Martineau à Yangambi, RD Congo. - MAINGOLO, LOBELA; BOYEMBA BOSELA Faustin,; LOSIMBA LO LIKOKE Rémy, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
The goal of this survey is to value the behavior of Guarea cedrata planted in White-Étoc and in Martineau leaving from some parameters dendrométriques notably the diameter to height of chest, the height was, the surface terrière and the volume was.             To the total, 190 stems of Guarea cedrata have been inventoried of which 76 stems in White-Étoc and 114 stems in Martineau of diameter superior or equal to 10 cm; what allowed us to value the structure periodic diamètrique of the aforementioned species enters 1977 and 2015 respectively; to value the middle yearly growths in Dhp, Hf, Ht, St. and the volume was under these two sylvan methods while taking into account the indication of stability of these populations under observation.             After analyses of data, he/it takes out again the results below:     - The structure diamètrique of Guarea cedrata was in the shape of bell in 1977 and in the shape of J reversed in 2015 in Martineau and in the shape of bell respectively in 1977 and 2015 White-Étoc coins;  - The middle yearly growths respectively in Dhp, in Hf and in St. uncross progressively with age; cross on the other hand in volume;  - The indication of stability or the factor of twinge remained however elevated in Martineau that in White-Étoc.